Pengaruh Karakteristik Struktural dan Manajerial Terhadap Efisiensi Usahatani Padi di Kabupaten Sleman - Triyono Triyono; Jangkung Handoyo Mulyo; Masyhuri Masyhuri; Jamhari Jamhari (Universitas Muhammadiyah Yogyakarta, 2016)
Efforts to increase productivity of food crops, especially rice by using technology and innovation has been facing problems such as structure of the control and management of agricultural resources. This study aimed to identify the factors of farmer’s structural and managerial characteristics that affect paddy farming efficiency in Sleman. Survey conducted on wetland rice farmers in rural and sub urban areas that represent the condition of the structural and manjerial characteristics that owned by farmers in Sleman. Analysis of stochastic frontier production function with the inclusion of the inefficiency effects model was conducted to identify determinants of production and the factors that affect the efficiency of farming. The result showed that the structural characteristics that influence the rice farming efficiency are the water irrigation source distance and the farm location, while the managerial characteristics factors are age, income outside the farm, participation in a group, experience and access to credit.